The competitiveness of the territory as the direction of social-geographical investigation - Олійник, Я.; Запотоцький, С. (Київський національний університет імені Тараса Шевченка, 2012)
The main components of the competitiveness of the territory are determined. The application of a spatial analysis as a tool of evaluation of territorial competitiveness and the analysis of the frame area as well as the justification of prospective directions of development of its elements are justified. The evaluation of the competitiveness of districts in the Cherkasy region is conducted and the their types are defined by the levels of competitiveness. Based on the received results the main junction and the centers of economic growth of Cherkasy region are selected and the prospects of improvement of their competitive position are defined.

Визначено основні складові формування конкурентоспроможності території. Обґрунтовано застосування територіально-просторового аналізу, як засобу оцінки територіальної конкурентоспроможності, аналізу каркасу території й обґрунтування перспективних напрямів розвитку його елементів. Проведено оцінку конкурентоспроможності районів Черкаської області, визначено типи районів області за рівнем конкурентоспроможності. На основі отриманих результатів виділено вузол та центри економічного зростання області, охаратеризовано перспективи покращення їх конкурентних позицій.
Конкурентоспроможність територій як напрям суспільно-географічних досліджень
Keywords: competitiveness of territory; frame area; competitive advantage; interregional competition; regional competitiveness; конкурентоспроможність території; каркас території; конкурентні переваги; міжрегіональна конкуренція; регіональна конкурентоспроможність